Discovery of highly potent and selective 7-ethyl-10-hydroxycamptothecin-glucose conjugates as potential anti-colorectal cancer agents - Yang, Chao; Xia, An-Jie; Du, Cheng-Hao; Hu, Ming-Xing; Gong, You-Ling; Tian, Rong; Jiang, Xin; Xie, Yong-Mei (Frontiers in Pharmacology, 2022)
7-Ethyl-10-hydroxycamptothecin (SN38), a highly potent metabolite of irinotecan, has an anticancer efficacy 100-1000 folds more than irinotecan in vitro. However, the clinical application of SN38 has been limited due to the very narrow therapeutic window and poor water solubility. Herein, we report the SN38-glucose conjugates (Glu-SN38) that can target cancer cells due to their selective uptake via glucose transporters, which are overexpressed in most cancers. The in vitro antiproliferative activities against human cancer cell lines and normal cells of Glu-SN38 were investigated. One of the conjugates named 5b showed high potency and selectivity against human colorectal cancer cell line HCT116. Furthermore, 5b remarkably inhibited the growth of HCT116 in vivo. These results suggested that 5b could be a promising drug candidate for treating colorectal cancer.